MAT363 - Statistical Inference February 2021 - PPSM, Pusat Pengajian Sains Matematik (Universiti Sains Malaysia, 2021)
Please check that this examination paper consists of SIX (6) pages of printed material before you begin the examination. Instructions : Answer all FOUR (4) questions. There are totally 80 marks.